(untitled) (مجلة أبحاث قانونية, 2023)
According to the Libyan law of Qisas and Diyya, those who determine the penalty for the premeditated murderer are his/her victim’s awliya al-dam; if there is no pardon, the death sentence would be issued, yet if one wali al-dam pardoned, the murderer’s life would be spared and he/she had to bear the penalty of life imprisonment and pay diyya. This essential role of awliya al-dam should have made the legislator accurately define them, and in light of its silence, the author sought through this Paper to determine the scope of wilayat al-dam by limiting its requirements to inheritance, sound mind, and reaching the age of majority at the time of the crime. Therefore, the author believes that the awliya al-dam’s absence at the time of the crime does not affect their right to pardon the offender if they return before execution, but considering the minor heirs are not awliya al-dam should not exclude them from submitting to the rule prohibiting combining the compensation and diyya, because they are entitled to diyya as the victim’s heirs.